Sustainable Brand Engagement: Bridging Gamification and Dual-Dimensional Loyalty in Coffee Shops - Audisty Prana Hardayu; Nur Afifah; Erna Listiana (Universitas Negeri Semarang, 2025)
This study examines the impact of gamification on customer loyalty through sustainable brand engagement in Indonesia’s coffee shop industry. Despite rapid industry growth, customer loyalty remains relatively low, prompting an investigation into how gamification elements influence sustainable brand engagement and both transactional and non-transactional loyalty dimensions. Employing a quantitative approach, data were collected from 350 respondents who are customers of local coffee shops across Indonesia’s five main islands. Partial Least Squares analysis was utilized to test inter-variable relationships. Results demonstrate that gamification significantly influences sustainable brand engagement, which subsequently exhibits strong effects on both loyalty dimensions. Notably, gamification shows no direct significant impact on loyalty, indicating full mediation through sustainable brand engagement. This study contributes theoretically by developing an integrative model that analyzes gamification’s influence on two distinct loyalty dimensions within Indonesia’s socio-cultural context. Findings imply the importance of designing gamification elements that build emotional connections and brand communities, rather than focusing solely on transactional aspects.